Dairy pathogens: Characteristics and impact - Papademas, Photis; Aspri, Maria (My University, 2014)
© 2015 by Taylor & Francis Group, LLC. Milk and dairy products can be an ideal medium for the growth of a variety of microorganisms, both pathogenic and spoilage. Even though milk and milk products are amongst the safest food worldwide and account only a small percentage of all food-borne diseases, they have an inherent potential for causing illness as they are potentially the source of a very broad range of microbial, chemical, and physical hazards. The presence of food-borne pathogens in milk and milk products is due to direct contact with contaminated sources in the dairy farm environment, to excretion from the udder of an infected animal and during processing and handling.
Keywords: Listeria monocytogenes; Listeriosis; Monocytogenes isolated